EFEKTIVITAS METODE PENGASAPAN BERBAHAN LIMBAH KAYU JATI (Tectona grandis) TERHADAP KEAWETAN KAYU DAMAR (Agathis sp.): The Effectiveness of Smoking-Method preservatives using Teak (Tectona grandis) Wood Waste to The Durability of Agathis Wood (Agathis sp) - Ade Firna; F Fitriaseh; Rika Faradhillah; Dian Sasmita; Andi Sri Rahayu Diza Lestari (PERENNIAL, 2021)
This study aimed to analyze the effectiveness of the smoking method using teak (Tectona grandis) wood waste in the agathis (Agathis sp) wood preservation process. The smoking process was done by putting teak wood waste into the combustion chamber and inserting agathis wood into the smoke room. The smoking duration was divided into 6 hours, 9 hours, and 12 hours with a maximum temperature ±70°C. The analysis carried out was an analysis of the chemical compound using GC-MS pyrolysis and testing the termite based on SNI 7207-2014. The results of GC-MS showed that the resin wood treated with smoking contained anti-termite compounds, namely phenolic, phenyl, and acid compounds, with the highest composition of 92.76% obtained from the duration of 12 hours of smoking. The termite test results showed that untreated wood had a higher weight loss and lower termite mortality than smoked wood. Meanwhile, the longer the smoking process, the lower the wood weight loss with the same mortality rate of 100%. It can be concluded that the smoking method using teak wood effectively increases the durability value of agathis against termites Coptotermes curvignathus.